2020
DOI: 10.3390/ijms21093126
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog Signal Inhibitor GANT61 Inhibits the Malignant Behavior of Undifferentiated Hepatocellular Carcinoma Cells by Targeting Non-Canonical GLI Signaling

Abstract: The Hedgehog (HH)–GLI pathway plays an important role in cell dedifferentiation and is therefore pivotally involved in the malignant transformation of cancer cells. GANT61, a selective inhibitor of GLI1 and GLI2, was reported as a promising treatment for cancer in various tissues; however, the biological impact of GANT61 in hepatocellular carcinoma (HCC), especially in undifferentiated HCC cells, remains unclear. In this study, we investigated the antitumor effect of GANT61 using two undifferentiated hepatoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…Recent studies identified novel non-canonical regulation of GLI in various cancers. Especially, nuclear myocardin-related transcription factor in basal cell carcinoma [ 57 ], deregulated GSK3β in colon cancer cells [ 58 ], Ras–Raf–MEK ERK pathway in hepatocellular carcinoma [ 59 ], fibroblast-derived insulin-like growth factor-1 in oral squamous cell carcinoma [ 60 ], MAPK/ERK signaling in lung adenocarcinoma [ 61 ], transcriptionally-active androgen receptors in pancreatic cancer [ 62 ] and SOX2-BRD4 transcriptional complex in melanoma [ 63 ]. Additionally, studies in breast cancer models, EMT cells induce increased metastasis of weakly metastatic, non-EMT tumor cells in a paracrine manner, in part by non-cell autonomous activation of the GLI transcription factor.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies identified novel non-canonical regulation of GLI in various cancers. Especially, nuclear myocardin-related transcription factor in basal cell carcinoma [ 57 ], deregulated GSK3β in colon cancer cells [ 58 ], Ras–Raf–MEK ERK pathway in hepatocellular carcinoma [ 59 ], fibroblast-derived insulin-like growth factor-1 in oral squamous cell carcinoma [ 60 ], MAPK/ERK signaling in lung adenocarcinoma [ 61 ], transcriptionally-active androgen receptors in pancreatic cancer [ 62 ] and SOX2-BRD4 transcriptional complex in melanoma [ 63 ]. Additionally, studies in breast cancer models, EMT cells induce increased metastasis of weakly metastatic, non-EMT tumor cells in a paracrine manner, in part by non-cell autonomous activation of the GLI transcription factor.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, known inhibitors of the Hedgehog signaling pathway include GANT61, cyclopamine, and GANT58 [ 26 ]. GANT61 specifically blocks GLI1 in the Hedgehog signaling pathway and inhibits cell transcription and expression [ 27 ]. Multiple myeloma cells were treated with GANT61 as a Hedgehog signaling pathway blocker.…”
Section: Discussionmentioning
confidence: 99%
“…We observed a minimum expression of HDAC9 in the normal hepatic cell line HC and well-differentiated HepG2 and HuH1 hepatoma cells that retain a hepatic phenotype, such as hepatic gene expression and drug-metabolizing activities. In contrast, HDAC9 mRNA was positively detected in HLE and HLF cells, typical undifferentiated HCC cell lines that show a mesenchymal phenotype [ 14 , 15 , 16 ]. Consistent with previous reports, class I HDACs were ubiquitously expressed among the cell lines tested, suggesting that HDAC9, but not class I HDACs, may play a specific role in undifferentiated HCC cells [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…CSCs are a sub-population of tumor cells responsible for their initiation, recurrence, and metastasis. Previously, we observed a 0.1–1.0% sphere formation rate in HLE and HLF cells seeded in a low-attachment dish [ 16 ]. In this study, HDAC9 suppression significantly reduced the growth of these spheres in both cell lines.…”
Section: Discussionmentioning
confidence: 99%